2016
DOI: 10.4049/jimmunol.1502529
|View full text |Cite
|
Sign up to set email alerts
|

HDAC3 Is Required for the Downregulation of RORγt during Thymocyte Positive Selection

Abstract: To generate functional peripheral T cells, proper gene regulation during T cell development is critical. Here, we found that histone deacetylase 3 (HDAC3) is required for T cell development. T cell development in CD2-icre HDAC3 conditional knockout mice (HDAC3-cKO) was blocked at positive selection, resulting in few CD4 and CD8 T cells, and could not be rescued by a TCR-transgene. These SP thymocytes failed to upregulate Bcl-2, leading to increased apoptosis. HDAC3-cKO mice failed to downregulate RORγt during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 54 publications
2
42
0
Order By: Relevance
“…ChIP assays revealed that HDAC3 directly deacetylates histones to inhibit RORγt gene expression. The deletion of RORγt and transgenic expression of Bcl-xl corrects the positive selection defect in HDAC3-cKO mice [86]. HDAC3 is also required for T cell development from DN stage 4 into the early CD4/CD8 DP stage.…”
Section: T Cellmentioning
confidence: 98%
“…ChIP assays revealed that HDAC3 directly deacetylates histones to inhibit RORγt gene expression. The deletion of RORγt and transgenic expression of Bcl-xl corrects the positive selection defect in HDAC3-cKO mice [86]. HDAC3 is also required for T cell development from DN stage 4 into the early CD4/CD8 DP stage.…”
Section: T Cellmentioning
confidence: 98%
“…RORgT is a crucial TF involved in the development of Th17 lymphocytes from naive CD4 + cells [7], and although its regulation at the transcription level in mouse models and in humans is well understood [3,21,31,32], how the gene is regulated epigenetically remains elusive. There is increasing evidence that various HDACs are involved [29,30], although treatments with HDAC inhibitors have led to different, sometimes conflicting, results [29,[45][46][47][48]. In this report, we investigated how HDAC inhibitors influence human RORgT expression in 3 cellular models: primary CD4 + cells differentiating toward Th17 cells, differentiated Th17 lymphocytes, and the Jurkat T cell line.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of HDAC activity in the regulation of the Rorgt gene was recently demonstrated using conditional knockout mice: Hdac3 was shown to be necessary for the inhibition of Rorgt gene expression during thymocyte-positive selection [30]. Using TNF-a inhibitors, as well as anacardic acid (an acetyltransferase inhibitor), Lin et al [34] were able to down-regulate Rorgt expression in a process associated with a decrease in histone acetylation in its promoter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because HDAC3 is the main HDAC member associated with NCOR1 corepressor complexes, one might expect that loss of HDAC3 in T cells leads to similar phenotypes. Indeed, several studies showed that HDAC3 is an important regulator of T cell development as well as of T reg cell functions . Early deletion of HDAC3 in common lymphoid progenitor cells (CLPs) using the Cd2 ‐iCre transgene (HDAC3‐cKO iCd2 ) or in DN thymocytes using the Lck ‐Cre deleter strain (HDAC3‐cKO Lck ) leads to a developmental block at the DP stage due to a defect in positive selection, which is reminiscent of the developmental alterations observed in NCOR1‐cKO Lck and NCOR1‐cKO Cd4 mice.…”
Section: T Cell Development In the Absence Of Ncor1 Or Hdac3—similar mentioning
confidence: 99%